Subdural empyema due to mixed infections successfully treated medically: A case report with review literature - Mostafa Meshref; Anas Zakarya Nourelden; Alaa Ahmed Elshanbary; Yossef Hassan AbdelQadir; Mohamed Sayed Zaazouee; Khaled Mohamed Ragab; Eman Mohammed Sharif Ahmed; Sarya Swed (Clinical Case Reports, 2022)
Abstract Subdural empyema is a rare intracranial infection with an accumulation of purulent material between the dura and arachnoid matter. We report a case of 17 years old presented with an altered conscious level. CSF analysis showed increased WBCs. His situation has improved after treating by acyclovir, ceftriaxone, vancomycin, and dexamethasone.